Moroccan EFL Public High School Teachers’ Perceptions and Self-Reported Practices of Assessment - Abderrahim Mamad; Tibor Vígh (Journal of Language and Education, 2021)
This study aims to investigate the perceptions and self-reported practices of Moroccan EFL public high school teachers towards traditional and alternative assessment. The data were collected from 51 teachers in Northern Morocco using a self-developed online questionnaire. The questionnaire items about teachers’ perceptions and self-reported practices were valid and both their data and sampling were acceptable for factor analysis of three subscales (traditional assessment, alternative assessment related with assessment as learning, and assessment for learning), and all scales proved to be reliable. Based on the three research questions, the study yielded the following results: (1) Teachers perceived the objectives of alternative assessment to be significantly more important than those of traditional assessment. (2) Based on their self-reported practices, teachers mainly used traditional assessment methods more often than alternative assessment methods associated with assessment as and for learning. (3) When comparing teachers’ perceptions with their self-reported practices, we found that teachers’ perceptions regarding traditional assessment matched their practices; while the majority of teachers admitted that they found alternative assessment important even though they did not often use it in order to support students to be able to reflect on their own learning or to enhance their performance in the learning process. Thus, these findings are significant for researchers, teachers, and educators to help them reconsider their perceptions of alternative assessment and how they should be enacted in practice with the aim of resolving the mismatches found in this study.